من الشكلانية الى البنيوية مسافة المفهوم والرؤية - رايس، كمال (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست - معهد الآداب واللغات, 2018)
Contextual methods had prevailed in the fild of literary criticism studies until the first half of the 20th century. then an evolution in philosophy of criticism generated a new approach to literary phenomenon that motivates critics to neglect all external influences considered as external themes and focuses on the study of the interior of text. thus appeared a new tendency knows as formalism. On the basis of formalism the structuralism theory was set based on a set of notions and principals striving for the secularizing the literary text. This contribution tries to describe the distance of the notion and perspective between the formalism and structuralism taking into account that the latter is methodically based on the first.
ظلت المناهج السياقية ""النفسية والاجتماعية والتاريخية مهيمنة على حقل الدراسات النقدية للأدب إلى غاية النصف الأول من القرن العشرين، حيث أدى التطور في فلسفة النقد إلى ميلاد تصور جديد في مقاربة الظاهرة الأدبية؛ يدعو إلى استبعاد المؤثرات الخارجية باعتبارها موضوعات خارجية والانطلاق من داخل النص. وهذا ما بات يعرف في ميزان النقد الأدبي بالشكلانية التي ركزت على شكل الأدب وانطلاقا من تأسيساتها النظرية تبلورت البنيوية مستندة إلى جملة من المفاهيم، والمبادئ هادفة إلى علمنة النص الأدبي؛ وفي هذه الورقة البحثية محاولة لتوصيف مسافة المفهوم والرؤية بين الشكلانية والبنيوية باعتبار الثانية تأسيسا منهجيا على الأولى.
Keywords: الأدب العربي -- الأدباء العرب -- النقد الأدبي -- الدراسات الأدبية -- الشكلانية -- البنيوية -- الدراسات اللغوية -- الدراسات الشعرية -- مستخلصات الأبحاث -- الترجمة